3x+4y+5z=4x+7y+6z

Simple and best practice solution for 3x+4y+5z=4x+7y+6z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+4y+5z=4x+7y+6z equation:


Simplifying
3x + 4y + 5z = 4x + 7y + 6z

Solving
3x + 4y + 5z = 4x + 7y + 6z

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3x + 4y + -4x + 5z = 4x + 7y + -4x + 6z

Reorder the terms:
3x + -4x + 4y + 5z = 4x + 7y + -4x + 6z

Combine like terms: 3x + -4x = -1x
-1x + 4y + 5z = 4x + 7y + -4x + 6z

Reorder the terms:
-1x + 4y + 5z = 4x + -4x + 7y + 6z

Combine like terms: 4x + -4x = 0
-1x + 4y + 5z = 0 + 7y + 6z
-1x + 4y + 5z = 7y + 6z

Add '-4y' to each side of the equation.
-1x + 4y + -4y + 5z = 7y + -4y + 6z

Combine like terms: 4y + -4y = 0
-1x + 0 + 5z = 7y + -4y + 6z
-1x + 5z = 7y + -4y + 6z

Combine like terms: 7y + -4y = 3y
-1x + 5z = 3y + 6z

Add '-5z' to each side of the equation.
-1x + 5z + -5z = 3y + 6z + -5z

Combine like terms: 5z + -5z = 0
-1x + 0 = 3y + 6z + -5z
-1x = 3y + 6z + -5z

Combine like terms: 6z + -5z = 1z
-1x = 3y + 1z

Divide each side by '-1'.
x = -3y + -1z

Simplifying
x = -3y + -1z

See similar equations:

| 208=-13n | | a+5+7=3(4+6a)-2(7a+3) | | 3a+7=2x-8b | | 2x-7/4=-8 | | 4x/x-y | | 2/3y=2/9 | | 4.6+1.4n=1.52 | | 14+20=10x+2x | | (2n-8)/(n-4) | | c-4/5=-1/3 | | 2=2-11 | | 3x+xy+3y=1 | | 400=20n | | 6x+7x=26 | | 3x^3+72=-72y | | 3z/10-4=4 | | 3=-g | | 25a^3+20a^2= | | 2x^2+28x=98 | | (5+x)(8x)=1220 | | (3x-2)^(1/2)=7 | | x+128+86+72=360 | | -4=r/2 | | 1/2x-1/4y=5 | | x+104+119+61=360 | | 10y-2y+11=3+8x+-4x | | x/9-6=-6 | | z/7-6=4 | | 1-4y=7-5y | | 21+2(50)=650 | | 0.15n+0.05(4250-n)=0.07(4250) | | 45+x+99+102=360 |

Equations solver categories